Properties of the Parabolic Anderson Model and the Anderson Polymer Model. (19th March 2013) - Cranston, Michael
Abstract : In this article we examine some properties of the solutions of the parabolic Anderson model. In particular we discuss intermittency of the field of solutions of this random partial differential equation, when it occurs and what the field looks like when intermittency doesn't hold. We also explore the behavior of a polymer model created by a Gibbs measure based on solutions to the parabolic Anderson equation.